Deep structure of the earth's crust in the area of the Krivoy Rog structure according to geological and geophysical data and the influence of the technogenic factor on the manifestation of local seismicity - V. V. Kutas; Yu. A. Andrushchenko; V. D. Omelchenko (Геофизический журнал, 2013)
Peculiarities of the Earth's crust structure in the area of the Krivoi Rog and Kremenchug suture zone located on the border of two megablocks of the Ukrainian Shield have been analyzed. The data obtained as a result of the SG-8 Krivoi Rog super-deep well drilling and geophysical works performance by seismic methods have been used. The results of comparison of the records and spectrograms of local earthquakes and industrial explosions in mines and quarries have been given. The origin of local seismicity with magnitude mb > 3,0 manifested in the zones of tectonic faults of the Earth's crust in the Krivoi Rog structure area during 2007-2011 in connection with technogenic loadings caused by mineral wealth mining with the application of powerful industrial explosions, has been considered.